The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.32604/oncologie.2022.025705
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis’s Role in Genitourinary System Cancer

Abstract: A cell is the basic unit of life, and death is inevitable for any cell. However, cancer cells that deviate from the normal track can resist death and survive. Ferroptosis is recently discovered as a modulated cell death different from other known forms of cell death in morphology, biochemistry, and genetics. It is characterized by irondependent lipid peroxidation regulated by various metabolic pathways. The incidence and mortality of genitourinary system cancer have been increasing recently. Although clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Sarcoglycan epsilon (SGCE) was progressively downregulated over time, following hypobaria–hypoxia exposure. Alternative splicing of SGCE exon 8 is regulated in a Sam68-dependent manner, plays a vital role in spermatogenesis and male fertility in mice, and may account for cell cycle arrest in response to hypoxia ( Paronetto et al, 2011 ; Liu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sarcoglycan epsilon (SGCE) was progressively downregulated over time, following hypobaria–hypoxia exposure. Alternative splicing of SGCE exon 8 is regulated in a Sam68-dependent manner, plays a vital role in spermatogenesis and male fertility in mice, and may account for cell cycle arrest in response to hypoxia ( Paronetto et al, 2011 ; Liu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…MFSD9 encodes a transport protein, but its function in cancer has not been reported. Autophagy mediated by transmembrane protein TMEM164 degrades ferritin to promote ferroptosis ( Liu et al, 2022 ; Liu et al, 2023a ). These genes were closely related to PPARs and they all have critical functions in cancer progression, indicating the complex roles of PPARs in STAD.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular iron homeostasis is precisely regulated by the iron metabolism system, and the maintenance of intracellular iron homeostasis is essential for cell function and fate [ 6 ]. The mechanism of ferroptosis, which has been found in a variety of tumors [ 7 , 8 ] and degenerative diseases, is also shown to be significantly associated with OA progression [ 9 , 10 ]. Previous studies have found that chondrocytes have various features of ferroptosis under pathological conditions: abnormal iron metabolism, lipid peroxidation, and mitochondrial dysfunction [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%